The role of lung-restricted autoantibodies in the development of primary and chronic graft dysfunction - Yang, Wenbin; Lecuona, Emilia; Wu, Qiang; Liu, Xianpeng; Sun, Haiying; Alam, Hasan; Nadig, Satish N.; Bharat, Ankit (Frontiers in Transplantation, 2023)
Lung transplantation is a life-saving treatment for both chronic end-stage lung diseases and acute respiratory distress syndrome, including those caused by infectious agents like COVID-19. Despite its increasing utilization, outcomes post-lung transplantation are worse than other solid organ transplants. Primary graft dysfunction (PGD) — a condition affecting more than half of the recipients post-transplantation — is the chief risk factor for post-operative mortality, transplant-associated multi-organ dysfunction, and long-term graft loss due to chronic rejection. While donor-specific antibodies targeting allogenic human leukocyte antigens have been linked to transplant rejection, the role of recipient's pre-existing immunoglobulin G autoantibodies against lung-restricted self-antigens (LRA), like collagen type V and k-alpha1 tubulin, is less understood in the context of lung transplantation. Recent studies have found an increased risk of PGD development in lung transplant recipients with LRA. This review will synthesize past and ongoing research—utilizing both mouse models and human subjects—aimed at unraveling the mechanisms by which LRA heightens the risk of PGD. Furthermore, it will explore prospective approaches designed to mitigate the impact of LRA on lung transplant patients.